Membangun Wirausaha di Kalangan Siswa Sekolah - Firmansyah; Masril (Jurnal Mitra Pengabdian Farmasi, 2021)
An entrepreneur is someone who will carry out an activity smartly and talentedly in introducing a product to consumers and is able to develop a product. It is very important to know that the condition of the people of the State of Indonesia to this day is abundant with a wealth of natural resources, therefore, as a society with education, do not only look for work but also must be able to create jobs by means of entrepreneurship. Based on the problems or events above, there are several ways that Vocational Schools or schools can do to minimize or suppress the number of unemployed in Indonesia, one of which is to provide entrepreneurial education to students from an early age, so that by giving views or directions on entrepreneurship, students are expected to have spiritual skills. high on the concept of entrepreneurship. Observing the various problems mentioned above, the PKM implementation team will try to offer a School-Based Entrepreneurship Model for Vocational High School Students (Vocational High Schools) with a case study at Ibnu Tamiyah Vocational School Pekanbaru. The result of this service activity is that based on this community service activity, it can be concluded that it is best and proper for every student to be given the ability or skill on how to open an effective and efficient entrepreneur.